First-Line Pazopanib Treatment in Metastatic Renal Cell Carcinoma: Real-World Data From a Single Chinese Center - Bin Wang; Ji-Wen Song; Hui-Qing Chen (Frontiers Media S.A., 2020)
The response to pazopanib in patients with metastatic renal cell carcinoma (mRCC) has been found to differ in Western and Eastern populations. Here, we analyzed the efficacy and side effects of pazopanib as first-line therapy in 31 consecutive patients with mRCC who were treated at a single Chinese center. Thirty-one consecutive patients with mRCC (20 males and 11 females, median age 59 years) were treated with pazopanib between October 2017 and July 2019. All patients had received a pathological diagnosis of RCC by prior radical nephrectomy or biopsy. All cases were treated with pazopanib (800 mg/day orally) as first-line therapy. Administration was continued until disease progression or unacceptable toxicities occurred. Objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and safety were evaluated. Twenty-nine patients were eligible for final analysis. At the median follow-up of 12.7 months, 34.5% (10/29) patients achieved a partial response (PR), 41.4% (12/29) patients had stable disease (SD), seven (24.1%) patients had disease progression (PD), and one patient had died. The ORR and DCR were 34.5% and 75.9%, respectively, and the median PFS was 10.1 months (95% confidence interval, 4.1-17.7 months). OS could not be determined. The most common side effects were fatigue (11 cases, 37.9%), hand-foot syndrome (10 cases, 34.5%), change of hair color (10 cases, 34.5%), elevated alanine transaminase (ALT)/aspartate transaminase (AST) (10 cases, 34.5%), hypertension (seven cases, 24.1%), neutropenia (three cases, 10.3%), anemia (three cases, 10.3%), thrombocytopenia (two cases, 6.9%), and diarrhea (one cases, 3.4%). Major (grade 3 or higher) adverse events included hand-foot syndrome (two cases, 6.9%) and thrombocytopenia (one case, 3.4%). Most adverse events were ameliorated by dose reduction or treatment interruption. Remissions occurred in almost all patients with local recurrence or pulmonary metastases, whereas PD occurred in patients with bone, liver or brain metastases. Our real-world data suggest that pazopanib is definitely efficacious as first-line therapy for mRCC, with well-tolerated side effects. Different metastatic lesions may have different sensitivity to pazopanib. An additional, large sample, multicenter, prospective study is needed to confirm our results.